1998
DOI: 10.1007/s005200050140
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral versus enteral nutrition in cancer patients: indications and practice

Abstract: Prospective randomly controlled trials have failed to demonstrate the clinical efficacy of providing nutritional support to most cancer patients in terms of morbidity, mortality, and duration of hospitalization. Serious shortcomings in study design have limited the possibility of drawing definitive conclusions from the data. Thus, nutritional intervention needs to be seen as a method of support, with the aim of maintaining nutritional and functional status during the stress of the oncology treatment to prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1
6

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 60 publications
0
27
1
6
Order By: Relevance
“…While indiscriminate use of postoperative total parenteral nutrition or enteral feeding is unwarranted [10], preoperative nutritional support should be implemented in cancer patients with malnutrition [11]. In this respect, the recent report in digestive tract cancer surgery of beneficial preoperative feeeding with supplemented enteral formula followed by postoperative jejunal feeding [12]might pave the way for similar minimally invasive support in malnutrition bladder cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…While indiscriminate use of postoperative total parenteral nutrition or enteral feeding is unwarranted [10], preoperative nutritional support should be implemented in cancer patients with malnutrition [11]. In this respect, the recent report in digestive tract cancer surgery of beneficial preoperative feeeding with supplemented enteral formula followed by postoperative jejunal feeding [12]might pave the way for similar minimally invasive support in malnutrition bladder cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer is the most common indication for the use of TPE as a method used for the delivery of nutrients directly into the blood, bypassing the decreased food intake and dysfunction of the gastrointestinal tract [57] . TPE has been shown to be appropriate for malnourished cancer patients receiving aggressive anticancer treatment, and to have a permissive role in those patients who cannot be given oncologic therapy because of a poor nutritional status.…”
Section: Total Parenteral Nutrition (Tpe)mentioning
confidence: 99%
“…TPE should be reserved for patients with gastrointestinal tract dysfunction due to an obstruction, peritoneal carcinomatosis, surgery, high output fi stula, fi brosis or major intestinal resections, who have a reasonable prognosis and cannot tolerate enteral feeding [57] . This category of patients can benefi t from long-term TPE at home, with TPE-related complications comparable to those seen in benign diseases.…”
Section: Total Parenteral Nutrition (Tpe)mentioning
confidence: 99%
“…However, several large studies showed that this drug has no significant impact on weight gain or any other benefit in patients with advanced colorectal cancer [120][121][122]. Increased survival times, improved appetite and increases in caloric intake and serum albumin levels have been reported with the use of hydrazine sulfate in some studies, but these favorable effects have not been confirmed by others [79]. Because of the lack of definitive studies showing consistent efficacy, together with the significant risk of neurotoxicity associated with its use, this drug has not gained popularity with oncologists [2,80].…”
Section: Other Potentially Useful Drugsmentioning
confidence: 99%
“…Finally, controversy remains regarding the influence of aggressive nutritional support on the quality of life of patients with advanced cancer, and it is very important to consider the risks, benefits and ethical aspects involved before beginning such a regimen. Physician attitudes, patient age and prognosis, and family or patient's perceptions often play important roles in the decision to administer nutritional support, and these variables will continue as issues during the patient's course [79].…”
Section: Nutritional Support With Cancer Cachexiamentioning
confidence: 99%